On the convective cores of MS rotating stars - Kuzmanovska, Olgica (National Library of Serbia, 2006)
An analysis of the influence of the uniform stellar rotation on masses and radii of convective cores of zero age stars is presented. The study also shows the dependence of the relative mass of the convective core on the parameters in the center (temperature, pressure) and on the surface (effective temperature, luminosity) of the star.
Keywords: Stars: interiors; Stars: rotation